Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0218534
|View full text |Cite
|
Sign up to set email alerts
|

Lower-dose prescriptions in the post-marketing situation and the influencing factors thereon

Abstract: The dosage of pharmaceuticals is determined through the process of clinical development and approval review based on clinical trial results; however, the information obtained from clinical trials before approval is limited. Some pharmaceutical products are used at doses lower than those approved for post-marketing use. The aim of this study was to reveal the actual state of lower-dose prescriptions for post-marketing clinical use of pharmaceuticals. We investigated the factors related to the deviation based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…An intriguing quantitative insight into the potential impact of nonadherence on dose response comes from the observation of drugs undergoing post‐marketing dose reduction. A recent study by Ogata et al 36 further supports the conclusions of two earlier papers, indicating that one in five drugs on the market is prescribed at a dosage at least 50% higher than required.…”
Section: Discussionsupporting
confidence: 55%
“…An intriguing quantitative insight into the potential impact of nonadherence on dose response comes from the observation of drugs undergoing post‐marketing dose reduction. A recent study by Ogata et al 36 further supports the conclusions of two earlier papers, indicating that one in five drugs on the market is prescribed at a dosage at least 50% higher than required.…”
Section: Discussionsupporting
confidence: 55%
“…Both ACEi and ARB medication doses were recorded and categorised into low and high dose (low dose = as per the British National Formulary initial dose or below maintenance dose; high dose = equal or greater than maintenance dose). Doses for hypertension in adults 18-75 years old were used if the British National Formulary (BNF) stated more than one indication or specific age group for a drug [25,26]. Sacubitril-valsartan was classified as an ARB.…”
Section: Variablesmentioning
confidence: 99%
“…The regulatory approved dosage regimens of drugs are usually derived from clinical trials results, however, post-marketing dosing variations are often observed in clinical practice. 19 …”
Section: Discussionmentioning
confidence: 99%